Short-term and Long-term Outcomes Following Pelvic Pouch Excision: The Mount Sinai Hospital Experience. Issue 12 (December 2020) - Pooni, Amandeep; de Buck van Overstraeten, Anthony; Cohen, Zane; MacRae, Helen M.; Kennedy, Erin D.; Brar, Mantaj S.
Abstract : BACKGROUND: Few studies have reported surgical outcomes following pouch excision and fewer have described the long-term sequelae. Given the debate regarding optimal surgical management following pouch failure, an accurate estimation of the morbidity associated with this procedure addresses a critical knowledge gap. OBJECTIVE: The objective of this study was to review our institutional experience with pouch excision with a focus on indications, short-term outcomes, and long-term reintervention rates. DESIGN: This was a retrospective cohort study. SETTING: This study was conducted at Mount Sinai Hospital, Toronto, Ontario Canada. PARTICIPANTS: Adult patients registered in the prospectively maintained IBD database with a diagnosis of pelvic pouch failure between 1991 and 2018 were selected. INTERVENTION: The patients had undergone pelvic pouch excision was measured. MAIN OUTCOMES AND MEASURES: Indications for excision, incidence of short-term and long-term complications, and long-term surgical reintervention were the primary outcomes. In addition, multivariable logistic regression models were fitted to identify predictors of chronic perineal wound complications and the effect of preoperative diversion. The positive predictive value of a clinical suspicion of Crohn's disease of the pouch was also evaluated. RESULTS: One hundred forty cases were identified. Fifty-nine percent of patients experienced short-term complications and 49.3% experienced delayed morbidity. Overall, one-third of patients required long-term reoperation related to perineal wound, stoma, and hernia complications. On multivariable regression, immunosuppression was associated with increased odds of perineal wound complications, and preoperative diversion was not associated with perineal wound healing. Crohn's disease was suspected in 24 patients preoperatively but confirmed on histopathology in only 6 patients. LIMITATIONS: This is a retrospective chart review of a single institution's experience, whereby complication rates may be underestimates of the true event rates. CONCLUSIONS : Pouch excision is associated with high postoperative morbidity and long-term reintervention due to nonhealing perineal wounds, stoma complications, and hernias. Further study is required to clarify risk reduction strategies to limit perineal wound complications and the appropriate selection of patients for diversion alone vs pouch excision in IPAA failure. See Video Abstract at http://links.lww.com/DCR/B348 . RESULTADOS A CORTO Y LARGO PLAZO DESPUÉS DE LA EXTIRPACIÓN DE LA BOLSA PéLVICA: LA EXPERIENCIA DEL HOSPITAL MOUNT SINAÍ: ANTECEDENTES: Pocos estudios han informado resultados quirúrgicos después de la escisión de bolsa pélvica (reservorio ileoanal) y menos han descrito las secuelas a largo plazo. Dado el debate sobre el manejo quirúrgico óptimo después de la falla de la bolsa, una estimación precisa de la morbilidad asociada con este procedimiento aborda una brecha crítica de conocimiento. OBJETIVO: El objetivo de este estudio fue revisar nuestra experiencia institucional con la extirpación de la bolsa con un enfoque en las indicaciones, los resultados a corto plazo y las tasas de reintervención a largo plazo. DISEÑO: Estudio de cohorte retrospectivo. ENTORNO CLINICO: Hospital Mt Sinaí, Toronto, Ontario, Canadá. PARTICIPANTES: Pacientes adultos registrados en la base de datos de EII mantenida prospectivamente con un diagnóstico de falla de la bolsa pélvica entre 1991 y 2018. INTERVENCIÓN: Escisión de bolsa pélvica. PRINCIPALES RESULTADOS Y MEDIDAS: Las indicaciones para la escisión, la incidencia de complicaciones a corto y largo plazo y la reintervención quirúrgica a largo plazo fueron los resultados primarios valorados. Además, se ajustaron modelos de regresión logística multivariable para identificar predictores de complicaciones de la herida perineal crónica y el efecto de la derivación preoperatoria. También se evaluó el valor predictivo positivo de una sospecha clínica de enfermedad de Crohn de la bolsa. RESULTADOS: Se identificaron 140 casos. El 59% de los pacientes desarrollaron complicaciones a corto plazo y el 49, 3% con morbilidad tardía. En general, 1/3 de los pacientes requirieron una reoperación a largo plazo relacionada con complicaciones de herida perineal, estoma y hernia. En la regresión multivariable, la inmunosupresión se asoció con mayores probabilidades de complicaciones de la herida perineal y la derivación preoperatoria no se asoció con la cicatrización de la herida perineal. La enfermedad de Crohn se sospechó en 24 pacientes antes de la operación, pero se confirmó por histopatología en solo 6 pacientes. LIMITACIONES: Revisión retrospectiva del cuadro de la experiencia de una sola institución por la cual las tasas de complicaciones pueden ser subestimadas de las tasas de eventos reales. CONCLUSIONES: La escisión de la bolsa se asocia con una alta morbilidad postoperatoria y una reintervención a largo plazo debido a complicaciones de heridas perineales, complicaciones del estoma y hernias. Se requieren más estudios para aclarar las estrategias de reducción de riesgos para limitar las complicaciones de la herida perineal y la selección adecuada de pacientes para la derivación sola versus la escisión de la bolsa en caso de falla de reservorio ileoanal. Consulte Video Resumen en http://links.lww.com/DCR/B348 .